RITATOON MEDIA DEVELOPMENT USING THE POE MODEL TO UNDERSTAND ADVICE SENTENCES - Maftuhah, Maftuhah; Sismulyasih SB, Nugraheti (Elementary School Teacher, 2019)
Based on pre-research in class III SDN Cangkiran 01 it was found that there were no suitable learning media and learning models. So it was been an impact on the low learning outcomes to understand the suggestion sentence. This study aims to develop learning media, assess the feasibility and effectiveness of ritatoon media using POE model class III SDN Cangkiran 01. The method which had been used in this research was Sugiyono Research and Development (RD) which consists of potential and problem stages, data collection, product design, design validation, design revisions, product trials, product revisions, and usage trials. The subjects of this study were grade III students at SDN Cangkiran 01. Data collection techniques used observation, interviews, documentation, questionnaires, and tests. Data analysis techniques were using product feasibility, initial and final data analysis (t-test and N-gain test). The results of the ritatoon media feasibility test that is from media experts get a percentage of 93% and the assessment of material experts get a percentage of 93%. Ritatoon media effectively used in accordance with the results of the t-test showed t arithmetic t table (12,741 2,021), then Ho was rejected and the pretest and posttest gain the result which was 0.62 with criteria that support the effectiveness of instructional media . The results of the questionnaire responses of teachers and students showed a very positive answer that makes learning media was more effective in its users.